1984
DOI: 10.1111/j.1600-079x.1984.tb00202.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Various Irradiances of Artificial Light, Twilight, and Moonlight on the Suppression of Pineal Melatonin Content in the Syrian Hamster

Abstract: The purpose of the present studies using artificial light was to determine how the timing and duration of exposure influence the light-induced suppression of pineal melatonin levels in hamsters. An 8-min exposure to 0.186 microW/cm2 of cool white fluorescent light caused a continued depression of pineal melatonin even when animals were returned to darkness. In addition, the pineal gland does not appear to change its sensitivity to light throughout the night. A 20-min exposure to 0.019 microW/cm2 of cool white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 22 publications
(12 reference statements)
2
29
1
Order By: Relevance
“…4). Brainard et al (1982Brainard et al ( , 1984 exposed Syrian hamsters to cool white fluorescent light during the peak of the hamster's nocturnal production of melatonin (7-10 hr after lightsoff). They found that within 8 min after experimental light exposure began, an illuminance of 1.08 lux significantly decreased pineal melatonin content, whereas 0.11 lux did not.…”
Section: Discussionmentioning
confidence: 99%
“…4). Brainard et al (1982Brainard et al ( , 1984 exposed Syrian hamsters to cool white fluorescent light during the peak of the hamster's nocturnal production of melatonin (7-10 hr after lightsoff). They found that within 8 min after experimental light exposure began, an illuminance of 1.08 lux significantly decreased pineal melatonin content, whereas 0.11 lux did not.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated for animals and suggested for humans that EMFs and light at night inhibit melatonin production [32][33][34]. Does this affect cancer risk and how?…”
Section: Relationship To Cancermentioning
confidence: 97%
“…The entraining effects of different spectra of light and their influence on reproduction are in need of investigation. Although the effect of exposure, during night, to various light irradiances and spectra on pineal metabolism are documented [11,22,23], studies pertaining to exposure during day (light phase) to the light spectra are rare. The present results underline the need for such studies.…”
Section: Discussionmentioning
confidence: 99%
“…Both artificial and natural light cycles influence the daily and annual rhythms of melatonin production [6][7][8][9] in a number of vertebrates. In Syrian hamsters, both the light irradiance and wavelengths are important in regulating the nocturnal rise in melatonin levels [10,11]. Clearly, light influences pineal gland activity, and the latter, in turn, has a regulatory role in reproduction [2].…”
Section: Introductionmentioning
confidence: 99%